Evaluating the Financial Performance of Nepalese Banks through the CAMELS Framework: A Theoretical Review - Pokharel, Sunil; Devkota, Niranjan (Journal of Economics and Management, 2025)
This study proposes a contextualized CAMELS rating framework for evaluating the financial performance of Nepalese banks in light of recent sectoral reforms. Given the banking sector’s pivotal role in sustaining economic stability and growth, the framework incorporates the six core CAMELS dimensions-Capital Adequacy, Asset Quality, Management Efficiency, Earnings Quality, Liquidity, and Sensitivity to Market Risk-while simultaneously addressing gaps identified in the existing literature. By incorporating Nepal-specific factors such as post-merger dynamics, regulatory changes, macroeconomic shocks, and digital transformation, the proposed model offers a comprehensive tool for assessing bank soundness. This framework aims to guide regulators, bank managers, and stakeholders in enhancing financial resilience and sustainable development within Nepal’s evolving banking environment.